Five Generations of Russian Constitutions: Russia as Part of the Western Legal Heritage - W. Butler (BRICS Law Journal, 2019)
The paper is devoted to the study of the relationship between the Russian constitutional history and Western legal traditions. The author argues the position according to which the constitutionalism has been a part of Russian legal history for centuries. On one view of Russian legal history, a written constitution remained an aspiration of the Russian people that was only partly realized in 1906. Marxist legal thought contemplated, or predicted, the “withering away of law” after a proletarian Revolution; adopting a constitution seemed counter-intuitive to this projected vector of history. This paper explores in general outline the five generations of the constitutions of Russia (1918, 1925, 1937, 1978, and 1993) and the maturing of a constitutional tradition in Russia which has led from a blueprint for communism to fully-fledged constitutional rule-of-law social State in which the constitution acts as a restraint upon the exercise of State power and performs the role that a constitution routinely performs as part of the western legal heritage. The author concludes the 1993 Russian Constitution is, for the first time, a living document that could be considered as a reaction against the Russian past, the embodiment of Russian experience, and the repository of Russian values and desires for its future.